Increased arterial stiffness elevates the risk of heart failure in diabetic patients - Wu, Lili; Wu, Meimei; Zhang, Xuelian; Chen, Shuohua; Wang, Guodong; Wu, Shouling; Zhuang, Jinqiang; Hong, Jiang (International journal of cardiology, 2023)
Previous studies have shown that arterial stiffness (AS) was a risk factor for heart failure (HF) in nondiabetic patients. We aimed to analyze this impact in a community-based diabetic population. Our study excluded those who had HF before brachial-ankle pulse wave velocity (baPWV) measurement and included 9041 participants finally. Subjects were divided into the normal (<14 m/s), intermediate (14–18 m/s), and elevated baPWV groups (>18 m/s) based on baPWV values. Multivariate Cox proportional hazard model was used to analyze the effect of AS on HF risk. During the median follow-up of 4.19 years, 213 patients had HF. The results of Cox model showed that HF risk in the elevated baPWV group was 2.25 times higher than that in the normal baPWV group (95% confidence interval [CI]: 1.24–4.11). HF risk increased by 18% (95% CI:1.03–1.35) for every 1 additional standard deviation(SD)of baPWV. Restricted cubic spline results showed statistically significant overall and non-linear associations between AS and HF risk (P < 0.05). The subgroup analysis and sensitivity analysis were consistent with that of total population. AS is an independent risk factor for developing HF in the diabetic population, and AS exhibits a dose-response relationship with HF risk. •AS was an independent risk factor for developing HF in the diabetic population.•AS exhibits a dose-response relationship with HF risk.